2020
DOI: 10.1109/access.2020.3034766
|View full text |Cite
|
Sign up to set email alerts
|

Software Vulnerability Analysis and Discovery Using Deep Learning Techniques: A Survey

Abstract: Exploitable vulnerabilities in software have attracted tremendous attention in recent years because of their potentially high severity impact on computer security and information safety. Many vulnerability detection methods have been proposed to aid code inspection. Among these methods, there is a line of studies that apply machine learning techniques and achieve promising results. This paper reviews 22 recent studies that adopt deep learning to detect vulnerabilities, aiming to show how they utilize state-oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 72 publications
(152 reference statements)
0
17
0
Order By: Relevance
“…Zou et al ( 2021) also developed a deep learning-based system for multiclass vulnerability detection to identify vulnerabilities in code. Zeng et al (2020) in their study reviewed research works that employed deep learning to detect software vulnerability. Those that used machine learning features are Lin et al (2018) who addressed issues when high quality training data is in deficit.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Zou et al ( 2021) also developed a deep learning-based system for multiclass vulnerability detection to identify vulnerabilities in code. Zeng et al (2020) in their study reviewed research works that employed deep learning to detect software vulnerability. Those that used machine learning features are Lin et al (2018) who addressed issues when high quality training data is in deficit.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…ere have been several survey articles providing systematic reviews of many approaches in this field from various perspectives [5,[28][29][30][31][32].…”
Section: Related Workmentioning
confidence: 99%
“…With the success of DL in fields such as image processing, speech recognition, and natural language processing, researchers have been increasingly motivated to apply DL for the SVP domain. Lin et al [13], Singh and Chatuvedi [26], and Zeng et al [16] all conducted an analysis of the deep learning techniques used by researchers for SVP.…”
Section: Existing Svp Reviewsmentioning
confidence: 99%
“…The SV data used to train a model is the most imperative component of this data-driven process. Although most studies have reported data preparation and data quality as significant issues for this research area [4], [10], [13], [16], [17], [24], they have not performed in-depth analysis of the data quality in SVP research to determine the encountered issues or potential solutions. This knowledge gap fails to provide practitioners and researchers with the specific insights needed to remediate data quality issues.…”
Section: Existing Svp Reviewsmentioning
confidence: 99%
See 1 more Smart Citation